Ontology Engineering Applications in Healthcare and Workforce Management Systems - Forbes, D.; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2017)
Looking beyond the communications technology horizon and projecting future competency-specific employment demand, this book presents an evaluation of desirable information systems enhancements by integrating two disparate-domain computer ...